Global burden of osteoarthritis from 1990 to 2019 attributable to high body mass index - Siming Yang; Licheng Zhou; Wanchen Gong; Bin Guo; Linfeng Wang (Archives of Medical Science)
Introduction The aim was to examine data from the Global Burden of Disease Study (GBD) 2019 to determine the global burden of osteoarthritis (OA) from 1990 to 2019 that is attributable to high body mass index (BMI).